\[\boxed{\text{213\ (213).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ \left( \text{ab} \right)^{6} = a^{6} \cdot b^{6}\]
\[2)\ \left( \text{mnp} \right)^{5} = m^{5} \cdot n^{5} \cdot p^{5}\]
\[3)\ (3c)^{7} = 3^{7} \cdot c^{7}\]
\[4)\ ( - 8xy)^{3} = ( - 8)^{3} \cdot x^{3} \cdot y^{3}\]
\[5)\ ( - 0,2cd)^{4} = ( - 0,2)^{4} \cdot c^{4} \cdot d^{4}\]
\[6)\ \left( \frac{3}{7}\text{kt} \right)^{9} = \left( \frac{3}{7} \right)^{9} \cdot k^{9} \cdot t^{9}\]
\[\boxed{\text{213.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1) - 0,2 \cdot (4b - 9) + 1,4b =\]
\[= 0,6b + 1,8\]
\[Получим\ из\ левой\ части\ \]
\[правую:\]
\[- 0,8b + 1,8 + 1,4b =\]
\[= 0,6b + 1,8\]
\[0,6b + 1,8 = 0,6b + 1,8.\]
\[Тождество\ доказано.\]
\[2)\ (5a - 3b) - (4 + 5a - 3b) =\]
\[= - 4\]
\[Получим\ из\ левой\ части\ \]
\[правую:\]
\[- 4 = - 4.\]
\[Тождество\ доказано.\]
\[3)\ 5 \cdot (0,4x - 0,3) + (0,8 - 0,6x) =\]
\[= 1,4x - 0,7\]
\[Получим\ из\ левой\ части\ \]
\[правую:\]
\[2x - 1,5 + 0,8 - 0,6x =\]
\[= 1,4x - 0,7\]
\[1,4x - 0,7 = 1,4x - 0,7.\]
\[Тождество\ доказано.\]
\[= \frac{1}{6}y\]
\[Получим\ из\ левой\ части\ \]
\[правую:\]
\[\frac{3}{9}y - \frac{27}{9} - \frac{2}{12}y + 3 = \frac{1}{6}y\]
\[\frac{2}{6}y - \frac{1}{6}y = \frac{1}{6}y\]
\[\frac{1}{6}y = \frac{1}{6}\text{y.}\ \]
\[Тождество\ доказано.\]